1997
DOI: 10.1128/iai.65.10.4038-4042.1997
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against gangliosides and Campylobacter jejuni lipopolysaccharides in Miller Fisher syndrome

Abstract: Seven patients with Miller Fisher syndrome (MFS), six in the acute phase and one in the recovery phase, were investigated for serum antibodies against gangliosides and purified lipopolysaccharides (LPS) from different strains of Campylobacter jejuni, including the MFS-associated serotypes O:2 and O:23. Immunoglobulin G antibodies against gangliosides GT1a and GQ1b were found in five of six patients in the acute phase of disease. Three of these patients also displayed antibodies to ganglioside GD2, a finding no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
1
16
0
2
Order By: Relevance
“…LPS from C. jejuni have been suggested as candidate antigens for triggering the induction of antibodies against gangliosides through the mechanism of molecular mimicry by oligosaccharide epitopes (2,3,26,39). With respect to MFS, this possibility has been supported by antibody cross-reactivity between GQ1b and LPS from MFS-linked C. jejuni serotypes, demonstrated with monoclonal anti-GQ1b antibodies (40) as well as with MFS patient antisera in our earlier study (20). The distinct patterns of antibody against GQ1b in MFS/resp and MFS/ gast patients may argue in favor of a causal relationship between infectious illness and neurological disease via the priming of an anti-GQ1b immune response.…”
Section: Discussionmentioning
confidence: 72%
“…LPS from C. jejuni have been suggested as candidate antigens for triggering the induction of antibodies against gangliosides through the mechanism of molecular mimicry by oligosaccharide epitopes (2,3,26,39). With respect to MFS, this possibility has been supported by antibody cross-reactivity between GQ1b and LPS from MFS-linked C. jejuni serotypes, demonstrated with monoclonal anti-GQ1b antibodies (40) as well as with MFS patient antisera in our earlier study (20). The distinct patterns of antibody against GQ1b in MFS/resp and MFS/ gast patients may argue in favor of a causal relationship between infectious illness and neurological disease via the priming of an anti-GQ1b immune response.…”
Section: Discussionmentioning
confidence: 72%
“…Gram-negative bacteria include Escherichia coli, Salmonella, Shigella, Pseudomonas, Helicobacter, Legionella, and Wolbachia. As an endotoxin, LPS increases the negative charge of the bacterial membrane and promotes the upregulation of pro-inflammatory cytokines, which contributes to gut dysbiosis [13,[25][26][27][28][29][30]. Heavy colonization of Gram-negative bacteria is followed by the release of LPS, which infiltrates through the intestinal barrier into the systemic circulation [13].…”
Section: Gut-derived Lipopolysaccharidesmentioning
confidence: 99%
“…Evidence indicates that bacterial LPS can elicit antibodies that cross-react with host nuclear materials [19]. Systemic LPS and the immune response against it has been shown to play a role in multiple disorders, including the opening of intestinal tight junctions, dysregulation of the BBB, neuroinflammation and neuroautoimmune disorders [25,[31][32][33][34][35][36][37][38][39]. Candido et al found that increased LPS translocation is one of many factors that can lead to dysbiosis [40].…”
Section: Gut-derived Lipopolysaccharidesmentioning
confidence: 99%
“…Nowadays, the leading hypothesis for the pathogenesis of GBS and peripheral nerve damage is a molecular mimicry, invoking an immune response to antigenic targets that are coincidentally shared by an infectious organism and nerve tissue. 14,15 Inflammatory infiltrates, which contain T lymphocytes and macrophages, cause demyelination and subsequent axonal degeneration by direct cytotoxic effects and releasing of inflammatory mediators, such as cytokines and nitric oxide.…”
Section: Myasthenic Syndromes Should Also Be Considered In Differentimentioning
confidence: 99%